2013
DOI: 10.1016/j.fob.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of the RS motif in N‐terminal head domain of goldfish germinal vesicle lamin B3 necessary for phosphorylation of the p34cdc2 target serine by SRPK1

Abstract: The nuclear envelopes surrounding the oocyte germinal vesicles of lower vertebrates (fish and frog) are supported by the lamina, which consists of the protein lamin B3 encoded by a gene found also in birds but lost in the lineage leading to mammals. Like other members of the lamin family, goldfish lamin B3 (gfLB3) contains two putative consensus phosphoacceptor p34cdc2 sites (Ser-28 and Ser-398) for the M-phase kinase to regulate lamin polymerization on the N- and C-terminal regions flanking a central rod doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Moreover, fish and amphibian lamins B3 contain SR/RS dipeptide motifs specific for serine/arginine protein kinases (SRPKs). Such a motif is present in four copies in goldfish and torafugu, in three copies in zebrafish, and in one and two copies in Xenopus lamin A/B3 and B1/B2, respectively [ 54 ]. This motif is also present in invertebrates: Ce-lamin has four copies, lamin C from D. melanogaster has two copies and lamin Dm has a single copy.…”
Section: Sequence Conservation and Phosphorylation In The Head Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, fish and amphibian lamins B3 contain SR/RS dipeptide motifs specific for serine/arginine protein kinases (SRPKs). Such a motif is present in four copies in goldfish and torafugu, in three copies in zebrafish, and in one and two copies in Xenopus lamin A/B3 and B1/B2, respectively [ 54 ]. This motif is also present in invertebrates: Ce-lamin has four copies, lamin C from D. melanogaster has two copies and lamin Dm has a single copy.…”
Section: Sequence Conservation and Phosphorylation In The Head Domainmentioning
confidence: 99%
“…This may reflect the adaptation of lamins to the biology of organisms in which oocytes are stored in the ovaries for long periods of time in prophase (diplotene). For example, in goldfish a major component of the oocyte nuclear lamina is lamin B3, and when Cdk1 kinase is not active, a still unknown SRPK kinase phosphorylates lamin B3 at the Cdk1 site [ 54 , 55 ].…”
Section: Sequence Conservation and Phosphorylation In The Head Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…However, limited research has explored the genetic and functional diversification of this gene family. While some partial phylogenetic analyses of CLKs have been performed elsewhere 10,[12][13][14] , to date no study has demonstrated a complete eukaryotic timeline, which could offer valuable insights in predicting functional roles and diversification across species 15 . Similarly, whilst crystal structure comparisons of human CLK1-4 have been determined 1,2,16,17 , there exists a gap in evaluating the structural conservation of CLK homologs between different eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Fish and amphibian lamins contain additional SR/RS dipeptide motifs, which are targeted by serine/arginine protein kinases. This feature was hypothesized to reflect an adaptation of lamins to the biology of oocyte storage in ovaries over a long period of time (Yamaguchi et al, 2013).…”
Section: Caaxmentioning
confidence: 99%